The risk of cardiovascular disease in systemic sclerosis: a population-based cohort study. Issue 7 (17th August 2012) - Man, Ada; Zhu, Yanyan; Zhang, Yuqing; Dubreuil, Maureen; Rho, Young Hee; Peloquin, Christine; Simms, Robert W; Choi, Hyon K
Abstract : Objectives: To evaluate the risk of incident myocardial infarction (MI), stroke and peripheral vascular disease (PVD) in individuals with systemic sclerosis (SSc) in a general population context. Methods: We conducted a cohort study using a UK primary care database containing records from 1986 to 2011. SSc diagnoses, outcomes and cardiovascular risk factors were identified from electronic medical records. We conducted two cohort analyses: (1) MI and stroke, and (2) PVD, excluding individuals with prevalent disease at baseline for each analysis. We estimated HRs comparing SSc with age-, sex- and entry time-matched comparison cohorts, adjusting for potential cardiovascular risk factors. Results: Among 865 individuals with SSc (85.8% women, mean age 58.7 years), the incidence rates (IRs) of MI and stroke were 4.4 and 4.8 per 1000 person-years (PY), versus 2.5 and 2.5 per 1000 PY in the comparison cohort. The corresponding adjusted HRs were 1.80 (95% CI 1.07 to 3.05) for MI and 2.61 (95% CI 1.54 to 4.44) for stroke. Among 858 individuals with SSc (85.3% female, mean age 58.9 years), the IR of PVD was 7.6 per 1000 PY versus 1.9 per 1000 PY in the comparison cohort, with an adjusted HR of 4.35 (95% CI 2.74 to 6.93). Conclusions: These findings provide the first general population-based evidence that SSc is associated with an increased risk of developing MI, stroke and PVD. Further insight into disease mechanisms, as well as how disease subtype, organ involvement and medication use may alter these increased risks, is needed.